Pengaruh Model Pembelajaran SOLE (Self-Organised Learning Environment) Terhadap Kemampuan Memecahkan Masalah Siswa pada Mata Pelajaran Sosiologi di Fase E SMA Negeri 1 Nan Sabaris - Sinta Kharisma; Ike Sylvia (Universitas Negeri Padang, 2024)
This experimental quantitative study investigates the impact of the Self-Organized Learning Environment (SOLE) Learning Model on students' problem-solving abilities in Phase E Sociology subjects. Two classes were chosen: X.E 6 as the experimental group and X.E 8 as the control group. The research used four essay-based test questions, including a pretest. The results revealed a significant improvement in student problem-solving outcomes, evidenced by the pretest and posttest scores. The average pretest score was 34,72, while the average posttest score was 67,12, showing an increase of 32,4 points. The sample class data showed normality and homogeneity. A t-test at a significance level of 0.05, with Tcount (4,01) greater than Ttable (1.99), confirmed the hypothesis. The N-gain score analysis indicated an average N-gain score of 51. for the sample class, which falls into the medium category. In conclusion, the SOLE model significantly enhances student problem-solving abilities in Phase E at SMA Negeri 1 Nan Sabaris.